Combining Quantitative and Qualitative Data in the Study of Feeding Behavior in Male Wistar Rats - Casarrubea, Maurizio; Aiello, Stefania; Di Giovanni, Giuseppe; Santangelo, Andrea; Palacino, Manfredi; Crescimanno, Giuseppe (Frontiers in Psychology, 2019)
The first step in a behavioral study is represented by the organization of a suitable ethogram, that is, a formal description of individual components of the behavior. Then, each component of such a behavioral repertoire can be quantified (e.g., how many times it occurs, its duration, percent distribution, latency, etc.). However, it is our contention that the possibility to describe the behavior of a living being by means of hundreds or even thousands of numbers concerning isolated components, disjointed from the comprehensive behavioral architecture, does not imply the possibility to use those numbers to reconstruct the meaning of behavior. Such a level of comprehension requires a qualitative approach based on the analysis of behavioral structure and its underlying dynamics. By means of synergic utilization of quantitative and qualitative data a more complete description of a given behavior becomes available. In present study we discuss results obtained from observations of feeding behavior in two groups of male Wistar rats: a control group, under standard diet, and a second group, under hyperglycidic one. Results have been presented both in terms of quantitative evaluations and in terms of structural/qualitative ones, the latter obtained by means of T-pattern detection and analysis. As to quantitative results, mean durations showed a significant reduction of Walking and Feeding and an increase of Hind-Paw Licking and Body Grooming; concerning mean occurrences, a significant increase of Front-Paw Licking, Hind-Paw Licking and Body Grooming was present; percent distributions showed significant reductions for Walking and Feeding and a significant increase for all grooming activities. As to qualitative assessments, T-pattern analysis unveiled a clear-cut behavioral reorganization induced by the hyperglycidic diet. If on the one hand, 50 different T-patterns were detected in subjects under standard diet, on the other hand, 703 different T-patterns were discovered in animals under hyperglycidic treatment, with a highly significant increase of mean lengths and a significant reduction of mean occurrences of T-patterns. Synergic evaluation of results in terms of quantitative and qualitative aspects shows, in rats fed with hyperglycidic diet, an increased anxiety condition, likely dependent on food-related stimuli and suggestive of a pervasive craving-related behavior.